2014
DOI: 10.5339/qmj.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Qatar: A retrospective cohort study

Abstract: Background: We conducted a retrospective cohort study to evaluate the clinical manifestations, laboratory findings, complications and treatment of brucellosis in the State of Qatar. Methods: The medical records of patients in Hamad Medical Corporation, Doha, Qatar were reviewed from January 2000 to December 2006. History, various socio-demographic features, clinical and biochemical parameters, therapeutic features, and complications were retrospectively collected from the patient database. Results: Around thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Thus, this study did not investigate bacterial susceptibility with respect to rifamycin sodium. In a separate retrospective cohort study, a combination of doxycycline and streptomycin was found to be the preferred regimen followed by co-administration of doxycycline and rifampin; no relapse or therapeutic failures were detected following these regimens [ 23 ]. However, because rifampin can enhance the plasma clearance of doxycycline resulting in lower doxycycline levels [ 24 ], we suggest that alternative medicines or combinations of antibiotics should be adopted to improve curative effects and reduce patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study did not investigate bacterial susceptibility with respect to rifamycin sodium. In a separate retrospective cohort study, a combination of doxycycline and streptomycin was found to be the preferred regimen followed by co-administration of doxycycline and rifampin; no relapse or therapeutic failures were detected following these regimens [ 23 ]. However, because rifampin can enhance the plasma clearance of doxycycline resulting in lower doxycycline levels [ 24 ], we suggest that alternative medicines or combinations of antibiotics should be adopted to improve curative effects and reduce patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is a public health problem that can cause severe significant disability and complications ( 10 ). According to the annual report of world health organization (WHO), Iran is an endemic region ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…В інших працях було відмічено, що бруцельоз частіше зустрічається серед пацієнтів старшого віку [2,7]. Статевий розподіл серед наших хворих, а саме переважання осіб чоловічої статі (75,00%) співпадає з даними більшості дослідників [10,12], що можливо пов'язано з найбільш широким залученням чоловіків до роботи з тваринами та вживанням необробленої продукції тваринництва. Тоді як, інші дослідники вказують протилежне, що серед хворих на бруцельоз переважають особи жіночої статі [3,11].…”
Section: результати обговоренняunclassified